Ergonomic issue on student’s health during virtual learning in the post-pandemic age - Ma, Yong Zhuang (2023)
The title of this report is named Ergonomic Issues on Student's Health During Virtual Learning in the Post-Pandemic Age. The COVID-19 pandemic has forced many educational institutions to shift to virtual learning, which has led to an increase in ergonomic issues among students. Prolonged use of digital devices and poor workstation setup can lead to musculoskeletal pain, eye strain, and other health problems. Therefore, the main objective of this study is to identify the factors contributing to ergonomic issues on student's health during virtual learning in the post-pandemic age and investigate their relationship. This study will use a mixed-methods approach, combining existing documents and a questionnaire survey. The existing documents will be collected from online discussions and academic articles or papers, related to ergonomic issues during virtual learning. The questionnaire survey will be distributed to a sample of students to collect data on the prevalence of ergonomic issues, and health impacts. The study will target UTAR-Sungai Long students from various academic programs and levels, who have experienced virtual learning due to the COVID-19 pandemic in the post-pandemic age who have experienced virtual learning. The data collected from the existing documents and questionnaire survey will be analyzed using content analysis, descriptive statistics, and Spearman Correlation analysis. As a result, the findings indicate that only posture show significance in relation to student’s health during virtual learning in the post-pandemic age. In conclusion, this study aims to provide insights into the factors contributing to ergonomic issues on student's health during virtual learning in the post-pandemic age. The findings also can be used to inform policies and interventions to promote healthy virtual learning environments for students.